EURO-MUSCULUS/USPRM phantom recipe for (musculoskeletal) interventional ultrasound training - Salce, Gregorio; Jačisko, Jakub; Ricci, Vincenzo; Mezian, Kamal; Özçakar, Levent (European journal of physical and rehabilitation medicine, 2025)
Considering the growing role of ultrasound-guided procedures in musculoskeletal medicine, training as regards these interventions is pivotal. While hands-on training on cadavers can be considered optimal, it has several drawbacks, e.g., high cost, poor availability, and technical challenges regarding preservation. Apart from cadavers, different approaches to practicing needle guidance are taught in ultrasound workshops whereby phantoms from meat (e.g., chicken breast), cheese or gelatin are used. Likewise, this article aims to provide a detailed description as to how different gelatin-based phantoms can be prepared. In line with the EURO-MUSCULUS/USPRM (European Musculoskeletal Ultrasound Study Group/Ultrasound Study Group of the International Society of Physical and Rehabilitation Medicine) protocols/background, the authors describe particular basic and advanced phantoms to be used for practicing different technical/manual skills pertaining to common ultrasound-guided procedures. The present manuscript can be considered a practical and ready-to-use "recipe book" for readers who are interested in the wide spectrum of interventional ultrasound.
Keywords: fantomy radiodiagnostické; Physical and Rehabilitation Medicine; Phantoms, Imaging; Ultrasonography, Interventional; Clinical Competence; lidé; klinické kompetence; muskuloskeletální nemoci; Europe; Musculoskeletal Diseases; intervenční ultrasonografie; Evropa; Humans; rehabilitační lékařství